Eyeshield 21: Manga, Identitas, dan Perkembangan Olah Raga di Jepang - Kariko, Abdul Aziz Turhan (Bina Nusantara University, 2010)
Article presents manga and its development related to sport in Japan. This effort brings financial advantages because the society likes and makes it into national identity. Presentation begins with manga history, manga sport, dan Eyeshield 21. It is concluded that Eyeshield 21 has a positive impact for Japanese society because that comic teaches the importance of teamwork, overcoming obstacles, and achieving life goals; Japan has succeeded to develop manga into their own cultural contact that implies in their national identity, that is Manga Eyeshield 21.